Tissue on the Transferred Coracoid Graft After Latarjet Procedure: Histological and Morphological Findings. Issue 3 (March 2019) - Haeni, David L.; Lafosse, Thibault; Haggerty, Charles; Plath, Johannes; Kida, Yoshikazu; Sanchez-Brass, Matthieu; Wolf, Françine; Calvo, Emilio; Müller, Andreas M.; Barbero, Andrea; Lafosse, Laurent
Background: Anterior shoulder instability is a debilitating condition that can require stabilization via a Latarjet procedure. Purpose: The aim of this study was to characterize the histological composition of the articular-sided surface of the coracoid bone graft after Latarjet procedure. Specific features of cells isolated from the coracoid and graft tissues were assessed. Study Design: Case series; Level of evidence, 4. Methods: Tissue samples were harvested from 9 consecutive patients undergoing arthroscopic debridement and screw removal after arthroscopic or open Latarjet procedure. Tissues were processed histologically. In 2 patients, the samples were analyzed to assess specific cellular properties. Results: Safranin O staining indicated that glenoid tissues contained variable amounts of glycosaminoglycan (GAG) and round chondrocytic cells mainly organized in clusters. Graft tissues contained less GAG and were more cellular but were not organized in clusters and had variable morphological features. An association appeared to exist between the cartilage quality of glenoid tissues and that of the graft tissues. Cells isolated from glenoid and graft tissues exhibited similar proliferation capacity. Conclusion: The results of our analysis show that cells located at the articular-sided surface of transferred coracoid grafts demonstrate fibrocartilaginous properties and may have the capacity for chondral proliferation. Further studies are needed to confirm this observation and future application.